Contemporary Issues in Services Marketing - Sarin, Anil (Indian Journal of Marketing, 2007)
Recently, India has got recognition among the major economies of the world. It has been ranked the fourth economic power in the world after the USA, China and Japan. L.N.Mittal, Britain's richest man and chairman of Arcelor Mittal, the world's largest steel company said, "At present, no corporate or board meeting anywhere in the world is complete without India being discussed". Interestingly, there is a significant contribution of services in the economic growth story of India. There has been a fundamental shift in the India's commercial dealings with the outside world. India has emerged as the fastest growing nation in the global services trade with the jump of 34% in the exports of services in 2006. Ranked at the 12th position, the country's services exports totaled $73 billion while imports were $70 billion in 2006 according to World Trade Organisation - WTO report. Looking at the contribution of services in most of the economies in the world, the time has come when marketers should make themselves familiarize with contemporary issues in the areas of services marketing for the better economical growth of their country and their own organizations.